2006
DOI: 10.1055/s-2006-924153
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Glutamic Acid Decarboxylase Antibody Positivity and its Association with Insulin Secretion and Sensitivity in Autoimmune Thyroid Disease: A Pilot Study

Abstract: Our results suggest that the prevalence GAD-Ab in Hashimoto's thyroiditis is around 5%. GAD-Ab antibody positivity per se does not appear to be associated with any disturbances in insulin sensitivity or insulin secretion in this specific population. The presence of islet-cell autoimmunity does not seem to influence insulin secretion or action in normal glucose tolerant subjects with Hashimoto's thyroiditis in this pilot study. Whether the presence of GAD-Ab per se or along with other antibodies impairs insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…These results are comparable with studies previously reported (17)(18)(19). A Turkish study reported a prevalence of 5.1% GAD-positivity in 215 patients with Hashimoto's thyroiditis, which is a similar percentage as our finding of 6.6% (17).…”
Section: Graves'supporting
confidence: 92%
See 1 more Smart Citation
“…These results are comparable with studies previously reported (17)(18)(19). A Turkish study reported a prevalence of 5.1% GAD-positivity in 215 patients with Hashimoto's thyroiditis, which is a similar percentage as our finding of 6.6% (17).…”
Section: Graves'supporting
confidence: 92%
“…These results are comparable with studies previously reported (17)(18)(19). A Turkish study reported a prevalence of 5.1% GAD-positivity in 215 patients with Hashimoto's thyroiditis, which is a similar percentage as our finding of 6.6% (17). In Japanese studies, around 4% of Graves' patients and around 3-6% of Hashimoto's patients were positive for GAD-antibodies (18,19).…”
Section: Graves'supporting
confidence: 91%
“…[567891011] The GAD Ab was present in 3.4% (15/441) of nondiabetic HT patients compared to 1.1% prevalence among Swedish adult population in a study by Lethagen et al . [10] The GAD Ab was associated with a decreased insulin secretion capacity, and two of them developed DM during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[567891011] The presence of Ab against beta cells in HT patients put them at the risk of development of latent autoimmune diabetes in adults (LADA) in the future. The sensitivity of IA-2 Ab is better than GAD Ab for the diagnosis of LADA in some ethnicities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is difficult to comment on the absence or presence of variances in incidence rates of AITD between different geographical locations. Coexistence of T1D and AITD is common, with 15 to 30% of T1D subjects having AITD [44][45][46], whereas the prevalence of glutamic acid decarboxylase antibodies (GADAb) in AITD patients is around 5% [47,48]. There is a need to distinguish T1D with AITD (T1D+AITD, APS-3A) from T1D without AITD (T1D-AITD).…”
Section: Nomenclaturementioning
confidence: 99%